2005
DOI: 10.1021/jp051184c
|View full text |Cite
|
Sign up to set email alerts
|

Small Temperature Dependence of the Kinetic Isotope Effect for the Hydride Transfer Reaction Catalyzed by Escherichia coli Dihydrofolate Reductase

Abstract: The H/D primary kinetic isotope effect (KIE) for the hydride transfer reaction catalyzed by Escherichia coli dihydrofolate reductase (ecDHFR) is calculated as a function of temperature employing ensemble-averaged variational transition-state theory with multidimensional tunneling. The calculated KIEs display only a small temperature dependence over the temperature range of 5 to 45 °C. We identify two key features that contribute to canceling most of the temperature dependence of the KIE that would be expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
198
4
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(223 citation statements)
references
References 49 publications
20
198
4
1
Order By: Relevance
“…For example, Neria and Karplus (32) used transmission coefficient calculations and constrained molecular dynamics (MD) trajectories to determine that the protein environment in triosephosphate isomerase (TIM) is essentially rigid (i.e., dynamically unresponsive) on the timescale of the intrinsic reaction dynamics; this finding is consistent with the lack of longlengthscale dynamical correlations reported in the current study. Furthermore, Truhlar and coworkers (33,34) and Karplus and Cui (35) both demonstrated that quasi-classical tunneling coefficients for hydrogen transfer evaluated at instantaneous enzyme configurations in the transition state region fluctuate significantly with donor-acceptor motions and other local active-site vibrations, which is likely consistent with the direct observation of short-lengthscale dynamical correlations reported here. However, by using quantized molecular dynamics to sample the ensemble of reactive trajectories in DHFR catalysis and to perform nonequilibrium ensemble averages that directly probe dynamical correlation, we provide a framework for strengthening and generalizing these earlier analyses.…”
Section: Resultssupporting
confidence: 84%
“…For example, Neria and Karplus (32) used transmission coefficient calculations and constrained molecular dynamics (MD) trajectories to determine that the protein environment in triosephosphate isomerase (TIM) is essentially rigid (i.e., dynamically unresponsive) on the timescale of the intrinsic reaction dynamics; this finding is consistent with the lack of longlengthscale dynamical correlations reported in the current study. Furthermore, Truhlar and coworkers (33,34) and Karplus and Cui (35) both demonstrated that quasi-classical tunneling coefficients for hydrogen transfer evaluated at instantaneous enzyme configurations in the transition state region fluctuate significantly with donor-acceptor motions and other local active-site vibrations, which is likely consistent with the direct observation of short-lengthscale dynamical correlations reported here. However, by using quantized molecular dynamics to sample the ensemble of reactive trajectories in DHFR catalysis and to perform nonequilibrium ensemble averages that directly probe dynamical correlation, we provide a framework for strengthening and generalizing these earlier analyses.…”
Section: Resultssupporting
confidence: 84%
“…While studying ecDHFR for example, Garcia-Viloca et al (7) predicted a 2° KIE (which is a sensitive probe of the reaction's potential surface and was later confirmed experimentally (31)); Pu et al (8) could reproduce the trends of temperature dependence for 1° KIEs, and Agarwal et al (28) could reproduce and predict several experimental data. All these studies could address the role of protein motion and other mechanistic features that are not directly accessible by experimental studies.…”
Section: "Marcus Like" Models (Environmentally Coupled Tunneling)mentioning
confidence: 94%
“…Furthermore the essential role of DHFR in DNA synthesis and in a variety of anabolic pathways makes it a common target for antiproliferative therapeutics. Due to its biological and pharmacological importance, and it being a small monomeric enzyme, DHFR has been the subject of intensive structural and kinetic investigation over many years, serving as a paradigm of enzymatic systems in many experimental and theoretical studies (1)(2)(3)(4)(5)(6)(7)(8). † This work was supported by NIH R01 GM65368-01 and NSF CHE-0133117 to A.K.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some authors postulate dynamics as a key driving force in catalysis (1)(2)(3)(4), others have performed analyses showing activation free-energy reduction, which is an equilibrium property, to be the source of catalysis (6)(7)(8)(9)(10)(11)(12)(13)(14). Enzyme reactions, and particularly their dynamics, present formidable challenges for study, and progress requires a combination of theoretical, experimental, and computational approaches (5,(15)(16)(17)(18) (20). The physical steps of ligand association and dissociation have been shown to depend on movements between these two conformations (20,21).…”
mentioning
confidence: 99%